The global terrorist threat : set to grow in 2014 - Rohan Gunaratna (2014)
The past year has been the most violent since the beginning of the current wave of terrorism. Al Qaeda, though truncated, has become more influential globally via the web, guiding its associates to strike official and civilian targets. With the western withdrawal from Afghanistan in 2014 the Taliban-led terrorist sanctuary is likely to be revived to threaten stability and security worldwide.